Multimodality cardiac evaluation in patients with Multisystem Inflammatory Syndrome in Children (MIS-C) - Hend Abu Shady; Huda Marzouk; Sandra Wassily; Dina Haroun; Mahmoud Aboudeif (Egyptian Pediatric Association Gazette)
Abstract Background Multisystem inflammatory syndrome in children (MIS-C) is a serious condition, following severe acute respiratory syndrome coronavirus infection (SARS-CoV-2) infection, identified by fever and multiorgan involvement. Severe cardiac affection may occur, which necessitates early diagnosis and management. The aim of this study is to evaluate ventricular functions by3-dimensional speckle tracking echocardiography (3D-STE) in MIS-C patients and compare it to cardiac magnetic resonance imaging (cMRI) findings. Cardiac evaluation was done by using conventional echocardiography, tissue Doppler imaging (TDI), 3D-STE, and cMRI. Results Twenty-five MIS-C patients with cardiac affection were included in our study. 14 males and 11 females with mean age 6.68 ± 2.45 years. M-mode, 3D-STE, and cMRI detected left ventricle (LV) dilatation in 12%, 8%, and 76% of patients, respectively. Evidence of LV systolic dysfunction was identified by M-mode, 3D-STE, and cMRI in 12%, 60%, and 72% of patients respectively. We compared LV dimensions and systolic function using different modalities. Although ejection fraction (EF) was normal by M-mode, it was lower by 3D-STE and cMRI. Statistically significant evidence of LV dilatation was observed in cMRI more than in echocardiography. Myocarditis was recognized in 20% of patients based on Lake Louis criteria of cMRI. Regarding coronary assessment by echocardiography, isolated left main coronary artery (LMCA) dilation was detected in 32% of patients while isolated right coronary artery (RCA) dilatation was found in 8% of patients. 8% of patients had combined dilatation of LMCA and left anterior descending artery (LAD) dilatation, another 8% had combined dilatation of LMCA and RCA and only 4% had combined dilatation of LMCA, LAD, and RCA. Conclusion Cardiac MRI and 3D-STE have a vital role in the detection of subclinical myocardial dysfunction among MIS-C patients, that can be missed by conventional echocardiography which enables appropriate early management of these patients.